The Role of Technology in Enhancing the Competence of Islamic Education Teachers in the Digital Era - Wahidah Wahidah; Ani Cahyadi (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
The development of digital technology has brought significant changes to the field of education, including Islamic education. Islamic Education (PAI) teachers are required to possess competencies that encompass not only pedagogical and subject-matter expertise but also the ability to effectively utilize technology. This study aims to analyze the role of technology in enhancing the competence of Islamic Education teachers in the digital era. The method used is a literature review by examining various sources related to the integration of technology in learning. The findings indicate that technology plays an important role in improving teacher competencies, particularly in professional, pedagogical, and self-development aspects. The use of digital platforms, interactive learning media, and access to online learning resources enables teachers to improve the quality of instruction and student engagement. However, challenges such as limited digital literacy and unequal access to technology remain obstacles that need to be addressed. Therefore, continuous training and institutional support are necessary to help Islamic Education teachers adapt and optimize the use of technology in the learning process